Effect of Tibial Plateau Levelling Osteotomy on Cranial Tibial Subluxation in the Feline Cranial Cruciate Deficient Stifle Joint: An Ex Vivo Experimental Study - Bilmont, A.; Retournard, M.; Asimus, E.; Palierne, S.; Autefage, A. (Veterinary and Comparative Orthopaedics and Traumatology, 2018)
Objectives This study evaluated the effects of tibial plateau levelling osteotomy on cranial tibial subluxation and tibial rotation angle in a model of feline cranial cruciate ligament deficient stifle joint.Methods Quadriceps and gastrocnemius muscles were simulated with cables, turnbuckles and a spring in an ex vivo limb model. Cranial tibial subluxation and tibial rotation angle were measured radiographically before and after cranial cruciate ligament section, and after tibial plateau levelling osteotomy, at postoperative tibial plateau angles of +5°, 0° and –5°.Results Cranial tibial subluxation and tibial rotation angle were not significantly altered after tibial plateau levelling osteotomy with a tibial plateau angle of +5°. Additional rotation of the tibial plateau to a tibial plateau angle of 0° and –5° had no significant effect on cranial tibial subluxation and tibial rotation angle, although 2 out of 10 specimens were stabilized by a postoperative tibial plateau angle of –5°. No stabilization of the cranial cruciate ligament deficient stifle was observed in this model of the feline stifle, after tibial plateau levelling osteotomy.Clinical Significance Given that stabilization of the cranial cruciate ligament deficient stifle was not obtained in this model, simple transposition of the tibial plateau levelling osteotomy technique from the dog to the cat may not be appropriate.
Keywords: tibial plateau levelling osteotomy; cranial cruciate ligament; cat; feline